Design and optimization of conformal cooling channels for injection molding: a review - Kanbur, Baris Burak; Suping, Shen; Duan, Fei (International journal of advanced manufacturing technology, 2020)
The recent developments in the additive manufacturing make easier and affordable the fabrication of conformal cooling channels (CCCs) compared with the traditional machining techniques. Conformal cooling channels (CCCs) achieve better cooling performances than the conventional (straight-drilled) channels during the injection molding process since they can follow the pathways of the molded geometry while the conventional channels fail. Cooling time, total injection time, uniform temperature distribution, thermal stress, warpage thickness, etc. are some of the objectives that are improved via CCC applications. However, the CCC design process is more complex than the conventional channels; therefore, computer-aided engineering (CAE) simulations have significant importance for the effective and affordable design. This review study presents the main design steps of CCCs as follows: (1) a background of the CCC fabrication process is projected, (2) the thermal and mechanical models are presented with respect to the 1D analytical model, (3) the CAE-supported design criteria are discussed for the 3D models of CCCs and relevant mold materials, (4) some of the illustrative CAE simulations are explained in detail according to the computational thermal and mechanical objectives, and (5) the single- and multi-objective optimization procedures are defined. By following the aforementioned steps, clearer and effective CAE steps can be obtained for the designers before the on-site fabrication of CCCs.